2023
DOI: 10.3847/1538-4357/aca966
|View full text |Cite
|
Sign up to set email alerts
|

The High-resolution Soft X-Ray Spectrum of Nova Delphini 2013

Abstract: We present the high-resolution soft X-ray spectrum of Nova Delphini 2013. Two spectra were taken with the Low Energy Transmission Grating Spectrometer on the Chandra X-ray Observatory, on 2013 November 9 and 2013 December 6, 87 and 114 days after the nova eruption, respectively. The spectra are of very high statistical quality, and reveal clear spectral evolution between the two observations. The source is bright enough on the two occasions that the third spectral order, with resolving power up to ∼3000, can e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Thus, the main absorption feature of the X-ray spectra is consistent with our wind model. The effective temperature of the WD photosphere is about T ph = 3 × 10 5 K during days 88 to 115, much lower than the value of Milla & Paerels (2023). It should be noted that Nelson et al (2013) reported a temperature of kT ∼ 27 eV (T ∼ 3.1 × 10 5 K) for the Chandra X-ray spectrum of V339 Del on day 88, which is consistent with our 1.25 M ☉ WD (Ne2) model.…”
Section: Supersoft X-ray Light Curvesupporting
confidence: 84%
“…Thus, the main absorption feature of the X-ray spectra is consistent with our wind model. The effective temperature of the WD photosphere is about T ph = 3 × 10 5 K during days 88 to 115, much lower than the value of Milla & Paerels (2023). It should be noted that Nelson et al (2013) reported a temperature of kT ∼ 27 eV (T ∼ 3.1 × 10 5 K) for the Chandra X-ray spectrum of V339 Del on day 88, which is consistent with our 1.25 M ☉ WD (Ne2) model.…”
Section: Supersoft X-ray Light Curvesupporting
confidence: 84%
“…Since the X-rays started to rise ≈20 days earlier, by day 77 it could have already reached ∼2.5 × 10 14 cm. Interestingly, Nova Delphini 2013 was also observed with gratings late (days 87 and 114 there), featuring blueshifted C and N lines, but in absorption with the SSS as a back-lighter (Milla & Paerels 2023). The fast velocities at these late times led those authors to explain the absorption by a thin shell ejected early, as well, but now 10 15 cm away from the center.…”
Section: Comparing the Two Epochs: Evidence For A Standingmentioning
confidence: 95%
“…We can assume that we observe a small shell of material near the WD atmosphere that has recently been detached and is expanding, thus modeling the spectrum with a photoionization code for X-ray astronomy, assuming that the photoionizing source is a blackbody, whose temperature is a fit parameter. This has been done with varying results (Ness et al 2011;Orio et al 2021;Ness et al 2022;Milla & Paerels 2023). Sometimes, many shells have to be included to fit the spectra, introducing many variable parameters (Ness et al 2011), so the parameterization becomes more uncertain.…”
Section: The "Stormy" Luminous Supersoft X-ray Phasementioning
confidence: 99%